2009
DOI: 10.1167/9.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Search for gross illumination discrepancies in images of natural objects

Abstract: Shadows may be "discounted" in human visual perception because they do not provide stable, lighting-invariant, information about the properties of objects in the environment. Using visual search, R. A. Rensink and P. Cavanagh (2004) found that search for an upright discrepant shadow was less efficient than for an inverted one. Here we replicate and extend this work using photographs of real objects (pebbles) and their shadows. The orientation of the target shadows was varied between 30 and 180 degrees. Stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 28 publications
9
36
0
Order By: Relevance
“…Once the orientation difference became small (30-), however, search was slower with the upright (light-from-above for both target and distractors) than the inverted displays, just as reported by Rensink and Cavanagh (2004). This is in keeping with shadow processing being coarsely scaled, so that only large shadow discrepancies can be readily perceived (Lovell et al, 2009;Mamassian, 2004).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Once the orientation difference became small (30-), however, search was slower with the upright (light-from-above for both target and distractors) than the inverted displays, just as reported by Rensink and Cavanagh (2004). This is in keeping with shadow processing being coarsely scaled, so that only large shadow discrepancies can be readily perceived (Lovell et al, 2009;Mamassian, 2004).…”
Section: Introductionmentioning
confidence: 61%
“…That is, in the context of Rensink and Cavanagh's (2004) claims, an (easily perceived) inverted shadow "poppedout" among (hard-to-perceive) upright ones, whereas a (hard-to-perceive) upright shadow was well concealed among easily perceived inverted distractors (see also Rensink & Cavanagh, 1993). Similarly, Lovell, Gilchrist, Tolhurst, and Troscianko (2009) demonstrated faster search of natural images of heterogeneous pebbles with upright (light-from-above) shadows for one with a discrepant shadow inverted 180-(light-from-below) than vice versa. Lovell et al also showed how the orientation difference between target and distractors affects search speeds.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We speculate that this may relate to our tendency to process shading and shadows differently from material cues to object identity (see for example, Lovell, Gilchrist, Tolhurst, & Troscianko, 2009). Perhaps this tendency results in the undulations -which are simulated here only via shading -being slightly harder to process than the simulated reflectance changes.…”
Section: Discussionmentioning
confidence: 85%
“…4 Although cast shadows give effective 3D position information, 8 differences between shading and shadowing are not very well noticed. 9 Furthermore, we showed previously 10 that light direction estimation of cast shadows do not follow the rules of linear perspective, much like the errors Canaletto made in the painting in figure 1.…”
mentioning
confidence: 79%